1998
DOI: 10.1038/sj.onc.1201768
|View full text |Cite
|
Sign up to set email alerts
|

PCR display identifies tamoxifen induction of the novel angiogenic factor adrenomedullin by a non estrogenic mechanism in the human endometrium

Abstract: Tamoxifen is currently the most widely used drug for the treatment of breast cancer, but there now exists considerable evidence that tamoxifen can also induce endometrial hyperplasia in pre menopausal women. We have used PCR di erential display on primary human endometrial isolates in an attempt to identify genes induced by tamoxifen but not estrogen. Eight such di erentially expressed bands were cloned and sequenced, one of which was found to be the peptide adrenomedullin. We have shown that adrenomedullin is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
115
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(124 citation statements)
references
References 22 publications
9
115
0
Order By: Relevance
“…Adverse effects of TAM on the endometrium include hyperplasia, malignancy and uterine bleeding all of which involve angiogenesis. We have examined the expression of a number of well characterized angiogenic factors in the endometrium of pre-and postmenopausal women receiving TAM therapy, namely aFGF, bFGF, TP, VEGF and ADM. Apart from ADM (Zhao et al, 1998), previous studies have mainly examined carcinoma lines or rodent uteri but not human tissues and not in relation to menopausal status. From the work described here, it appears TAM is capable of modulating the expression of these angiogenic factors, both in terms of the expression level and profile with aFGF, bFGF and ADM being upregulated especially in premenopausal tissue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Adverse effects of TAM on the endometrium include hyperplasia, malignancy and uterine bleeding all of which involve angiogenesis. We have examined the expression of a number of well characterized angiogenic factors in the endometrium of pre-and postmenopausal women receiving TAM therapy, namely aFGF, bFGF, TP, VEGF and ADM. Apart from ADM (Zhao et al, 1998), previous studies have mainly examined carcinoma lines or rodent uteri but not human tissues and not in relation to menopausal status. From the work described here, it appears TAM is capable of modulating the expression of these angiogenic factors, both in terms of the expression level and profile with aFGF, bFGF and ADM being upregulated especially in premenopausal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry was carried out as previously described (Zhao et al, 1998). Briefly, slides were incubated with 5% goat serum (Dako) to reduce non-specific background staining, followed by 1 out of 800 anti-adrenomedullin (Peninsula Laboratories, Liverpool, UK).…”
Section: Adrenomedullin Immunohistochemical Stainingmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1998, we first showed ADM to be potently angiogenic using the chick chorioallantoic membrane assay (Zhao et al, 1998), and it has subsequently been shown to be protumorigenic by a number of groups employing both xenograft studies Oehler et al, 2002) and blocking antibodies (Ouafik et al, 2002). Adrenomedullin and cancer have recently been reviewed (Zudaire et al, 2003).…”
mentioning
confidence: 99%